A Survey of career status identity on student college - Kusuma, Kusumawati; Suwarjo, Suwarjo (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
One of the concerns in the process of adolescent transition into adulthood is the status of career identity. Good status enables teenagers to survive in increasingly competitive conditions. This study aims to see the status of career identity found in first year students at Yogyakarta State University. Data were collected by survey method using scale spread to 500 respondents. The scale used by SPSS to meet the validity and reliability The results show that 96% of respondents in the right field are in the category of achievement and 4% are in foreclosure category. While in the non-exact field there are 97% are in the category of achievement and 3% is foreclosure category. So it can be said that about 95% of respondents have good identity status, and expected to survive in an increasingly competitive conditions. This study contributes to literature of career identity status as well as other contributions described.